A new species of coralsnake (Micrurus: Elapidae) from southern Brazil - Di-Bernardo, Marcos; Borges-Martins, Marcio; Da Silva (Jr.), Nelson Jorge (Zootaxa, 2007)
A new species of triadal coralsnake (Micrurus) is described from Rio Grande do Sul, Brazil. The new species differs from other Micrurus species in southern Brazil by the following characters: snout mostly black, head completely black, white gular region, triads with middle black ring 1.5 to 2 times longer than the external black rings, white rings shorter than the external black rings. The new species occurs sympatrically with M. altirostris and adds to the following known triadal species for the region: M. baliocoryphus, M. pyrrhocryptus, M. lemniscatus, and Micrurus decoratus. Its current range is restricted to Rio Grande do Sul but it may reach adjacent areas of Argentina and Paraguay.